Effect of Oat-Based Ready-to-Eat 70 g Break-Fast on Appetite Control, Satiety and Perspective Food Intake Versus 55 and 35 g: A Randomized, Crossover Study - Vizbaraite, Daiva; Sujeta, Arturas; Balciunas, Mindaugas; Balciuniene, Vaiva; Nickus, Edas (Pakistan Journal of Nutrition, 2015)
Aim of the study was to establish the impact of most widely sold oat-based ready-to-eat breakfast cereal (RTEC) currently provided in different portions on appetite control until lunch. Thirty healthy participants (16 males and 14 females) were involved in a randomized double blind crossover study. Mean age -39±13.5; normal body mass index -22.3 kg/m2. Female subjects also completed a menstrual cycle questionnaire so that breakfast test days would fall within the luteal phase of the menstrual cycle. Participants kept records on amounts of food intake during the entire study period. The diet of the subjects was monitored throughout the entire survey process. The subjects had to eat in the usual way and not make any dietary changes. The subjects over a 9-day period daily consumed different RTEC breakfasts varied in dry weight (70, 55, 35 g). These different breakfast foods were selected randomly and taken for 9 consecutive days at the same time. Visual analog scales for appetite measurements were administered before breakfast at 07:00 and repeatedly until 12:00 before lunch. Paired t-tests were performed for comparison of appetite ratings between different products. This study showed that 70 g of RTEC versus 35 and 55 g reduced hunger, increased sensation of fullness, decreased desire to eat and satisfaction after meal were significantly prolonged and greater in every time point (p